Protein phosphatase 4 promotes chromosome pairing and synapsis, and contributes to maintaining crossover competence with increasing age. - Aya Sato-Carlton; Xuan Li; Oliver Crawley; Sarah Testori; Enrique Martinez-Perez; Asako Sugimoto; Peter M Carlton (PLoS Genetics, 2014)
Prior to the meiotic divisions, dynamic chromosome reorganizations including pairing, synapsis, and recombination of maternal and paternal chromosome pairs must occur in a highly regulated fashion during meiotic prophase. How chromosomes identify each other's homology and exclusively pair and synapse with their homologous partners, while rejecting illegitimate synapsis with non-homologous chromosomes, remains obscure. In addition, how the levels of recombination initiation and crossover formation are regulated so that sufficient, but not deleterious, levels of DNA breaks are made and processed into crossovers is not understood well. We show that in Caenorhabditis elegans, the highly conserved Serine/Threonine protein phosphatase PP4 homolog, PPH-4.1, is required independently to carry out four separate functions involving meiotic chromosome dynamics: (1) synapsis-independent chromosome pairing, (2) restriction of synapsis to homologous chromosomes, (3) programmed DNA double-strand break initiation, and (4) crossover formation. Using quantitative imaging of mutant strains, including super-resolution (3D-SIM) microscopy of chromosomes and the synaptonemal complex, we show that independently-arising defects in each of these processes in the absence of PPH-4.1 activity ultimately lead to meiotic nondisjunction and embryonic lethality. Interestingly, we find that defects in double-strand break initiation and crossover formation, but not pairing or synapsis, become even more severe in the germlines of older mutant animals, indicating an increased dependence on PPH-4.1 with increasing maternal age. Our results demonstrate that PPH-4.1 plays multiple, independent roles in meiotic prophase chromosome dynamics and maintaining meiotic competence in aging germlines. PP4's high degree of conservation suggests it may be a universal regulator of meiotic prophase chromosome dynamics.